Innovational Processing Model of Traditional Snack Klepon Craquelin Become a Culinary Icon of Surabaya City - mahmudi mahmudi; ivy dian puspitasari prabowo; tjhing man lie; Panca Rahmi Azzahra; Bryanda Arya Prabusta Martin; Diyan Lesmana; Woro Andrini (LPPM of NAROTAMA UNIVERSITY, 2025)
Traditional snacks are one of Indonesia's traditional culinary heritages that have significant cultural, social, and economic value. In the city of Surabaya, traditional snacks are not only seen as complementary foods, but also have the potential to become an instrument of food security and the city's culinary identity. However, with the development of more practical modern foods, the existence of traditional snacks is increasingly marginalized. This study aims to develop a traditional snack processing model based on innovation, branding, and empowerment of MSMEs to increase competitiveness while strengthening Surabaya's city branding. The product is made by making Klepon Craquelin cakes as part of the traditional klepon innovation that has been enjoyed by most of the general public, especially the people of Surabaya. The study used the implementation method in the Sages Academy laboratory and was conducted with a taste test. The results showed that Klepon Craquelin cakes as part of the traditional klepon innovation are a solution for local food diversification, encouraging the growth of MSMEs, and strengthening tourism attractions. This research is an innovation of traditional klepon market snacks that will become a new city branding for the city of Surabaya, so that traditional culinary is not only sustainable but also develops in a global context. Klepon Craquelin cake has a unique, contemporary taste that will be loved by Generation Z.